TAFAKKUR DALAM PERSPEKTIF AL-QUR’AN - Enghariano, Desri Ari (IAIN Padangsidimpuan, 2019)
Thinking is one of human privileges compared to other of God. In the uslub of qur’an, the word of this thought is expressed in the term tafakkur. Other terms that have some similaraties with it are ta’ammul and tadabbur. Tafakkur activity or thinking well and deeply is the key to opening the door of divine light, the door of all knowledge, the beginning or basis for the vision of conscience and the path to ma’rifatullah, so that it reaches a good understanding of Allah SWT. The urgency of tafakkur for a muslim is a form of self-reflection so that he can become a servant who is always gratefull. Tafakkur is very much beneficial if done accordingly. However, tafakkur has limits, among them : they can not bear testimony about the substance of God, do not harm, and tafakkur should make us more confident to God.